2007
DOI: 10.1112/jlms/jdm050
|View full text |Cite
|
Sign up to set email alerts
|

On subnormality criteria for subgroups in finite groups

Abstract: Let H be a subgroup of a finite group G

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Consider G to be the symmetric group on a set of 8 elements S 8 . As we already mentioned Fumagalli, in [24], observed that considering and calling H := h and A := a, b , we obtain that G = A, H . With a little calculation we proved that A and H are N 3 -connected subgroups, i.e.…”
Section: Examples Of N -Connected Subgroupssupporting
confidence: 52%
See 2 more Smart Citations
“…Consider G to be the symmetric group on a set of 8 elements S 8 . As we already mentioned Fumagalli, in [24], observed that considering and calling H := h and A := a, b , we obtain that G = A, H . With a little calculation we proved that A and H are N 3 -connected subgroups, i.e.…”
Section: Examples Of N -Connected Subgroupssupporting
confidence: 52%
“…In fact: consider a non nilpotent group G. If we put G = A = B, then A and B are trivially cosubnormal, but they are not N -connected. For the vice versa, the authors construct an example in [11] or alternatively we propose the following example in [24] Called H := h and A := a, b , it is possible to show that G = A, H and A and H are N 3 -connected subgroups, but for example H is not subnormal in G.…”
Section: Cosubnormality and N -Connectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently X, X g is a σ i -group and then X is σ-subnormal in X, X g for every g ∈ G by Lemma 1 (6). Applying Theorem A, X is σ-subnormal in G, a contradiction.…”
Section: Proofs Of the Main Theoremsmentioning
confidence: 89%